ATC Best Practices: An Opportunity for Computer-Based Scoring - Hubbar, Todd (Journal of aviation/aerospace education and research, 2006)
This paper explains how computer-based scoring of computer-generated scenarios in air traffic was designed and developed to meet the objectives of the Federal Aviation Administration (FAA). Radar Terminal Facility (RTF) instructors from the Air Traffic Division at the FAA Academy, other Certified Professional Controllers (CPC) from Miami and Chicago, and professional educators converged in September 2002 to design, develop, and implement a course that would enhance controller effectiveness by capturing controller best practices. These best practices were synthesized from a series of intensive air traffic control simulations in a fictional airspace. Programmers from the FAA Academy worked with subject matter experts to design and develop an objective means by which these simulations could be graded. The result was a modified version of an Academy invented program called SIGNAL. The newly enhanced software met the team's expectations and looked to have future applications in initial air traffic controller training. The success of SIGNAL has also had an effect on all pretest-posttest measures for other groups within the Academy.